Spontaneous functional full recovery from motor and sensory deficits in adult mice after mild spinal cord injury. Issue 6 (June 2019) - Kakuta, Yohei; Adachi, Anna; Yokohama, Marino; Horii, Toshiki; Mieda, Tokue; Iizuka, Yoichi; Takagishi, Kenji; Chikuda, Hirotaka; Iizuka, Haku; Nakamura, Kazuhiro
Abstract: The extent of spontaneous recovery in patients with a spinal cord injury (SCI) has not been thoroughly investigated. It is essentially not known whether SCI animals exhibit full recovery from both motor and sensory deficits as well. Here, we developed an appropriate condition to produce a mild SCI in mice. Mice given a mild contusion SCI showed transient low performances in the Basso Mouse Scale for locomotion (BMS), rotarod and beam walking tests after the SCI, which was followed by complete restoration in a short time. The SCI mice also showed functional full recovery from low sensitivity to light touch using dynamic touch test. Nevertheless, the fully-recovered SCI mice still exhibited significant loss of myelin in the spinal cord. These results suggest a high potential of adaptation of motor and sensory systems in mice and might provide insight into the prognoses of SCI patients.